Situation Report: Czechoslovakia, 8 June 1971 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. A New Creation: The Czech Writers' Union Czech Association for Science, Culture, and Politics Once Again a Chinese Ambassador in Prague Radio Forum: Questions from the Public Czech Writer Svatopluk Kadlec Dies